Comparison of Strength and Durability in Properties of Concrete with Partial Replacement of Ground Granulated Blast Furnace Slag - Sheetal Kumar; Bhojram (International Journal of Scientific Research in Civil Engineering, 2024)
Concrete is defined as the mixture of sand (FA) , Gravel (CA) and Water. it plays a very important role in the infrastructure development. the utilized material 2 of supplementary cementation should be accepted , since it give several properties in the concrete as well as economy. this paper present an investigation on the study of the effect of GGBFS On strength development of mortar and the optimum use of slag in mortar .Cement was partially replaced with seven percentage (40%, 42%, 44%, 46%,48%,50%) of slag by weight . Ordinary Portland cement (OPC) mortar was also prepared as reference mortar. A total of 42 cube and briquet mortar specimens were cast and compressive as well as tensile strength of the mortar specimens were determined at curing age of 7, 14 and 28 days. From the Test results we find that Ground granulated impact heater slag (GGBS) can be use for halfway substitution in cement.